Hyperperfusion syndrome after carotid stent angioplasty. - Grunwald, I; Politi, M; Reith, W; Krick, C; Karp, K; Zimmer, A; Struffert, T; Roth, C; Kühn, A; Haass, A; Papanagiotou, P (2009)
INTRODUCTION: This study assesses the incidence and causes of hyperperfusion syndrome occurring after carotid artery stenting (CAS). MATERIALS AND METHODS: We retrospectively reviewed the clinical database of 417 consecutive patients who were treated with CAS in our department to identify patients who developed hyperperfusion syndrome and/or intracranial hemorrhage. Magnetic resonance imaging (MRI) including fluid-attenuated inversion recovery and diffusion-weighted imaging was performed before and after CAS in 269 cases. A Spearman's rho nonparametric correlation was performed to determine whether there was a correlation between the occurrence/development of hyperperfusion syndrome and the patient's age, degree of stenosis on the stented and contralateral side, risk factors such as diabetes, smoking, hypertension, adiposity, gender and fluoroscopy time, and mean area of postprocedural lesions as well as preexisting lesions. Significance was established at p < 0.05. RESULTS: Of the 417 carotid arteries stented and where MRI was also completed, we found hyperperfusion syndrome in 2.4% (ten cases). Patients who had preexisting brain lesions (previous or acute stroke) were at a higher risk of developing hyperperfusion syndrome (p = 0.022; Spearman's rho test). We could not validate any correlation with the other patient characteristics. CONCLUSION: Extensive microvascular disease may be a predictor of hyperperfusion syndrome after carotid stent placement. We believe that further studies are warranted to predict more accurately which patients are at greater risk of developing this often fatal complication.